Magnetic Leakage Simulation of Converter Transformer and Shielding Analysis of Different Material Shielding Devices. Issue 7 (April 2020) - Zhou, Junfeng; Wang, Shuo; Peng, Chong; Wu, Peng; Wang, Ning; Yang, Shuqiang
Abstract: Due to the complex structure and large winding current of converter transformer, the magnetic flux leakage was more serious, which was prone to local overheating and affected the safe and stable operation of transformer. Therefore, it was necessary to study the distribution of magnetic flux leakage in transformer. In this paper, the three-dimensional model of 500kV converter transformer was established based on the actual drawings, and the magnetic flux of iron core, fuel tank and distribution of magnetic flux leakage between high and low voltage winding was calculated under time-harmonic field by using the finite element method. The shielding method combining strip shielding plate and lung lobe shielding device was adopted, and the influence of different material shielding devices on the distribution of magnetic flux leakage was compared and analysed. The research results showed that when the shielding device adopted new material, the maximum magnetic flux leakage of the fuel tank decreased to 0.22T, decreasing amplitude of 65.62%, and the magnetic flux leakage in winding space decreased by 20.83%, which significantly improved the shielding effect.